2014
DOI: 10.1289/ehp.1307063
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Phthalate Exposures and Neurobehavioral Development Scores in Boys and Girls at 6–10 Years of Age

Abstract: Background: There is concern over potential neurobehavioral effects of prenatal phthalate exposures, but available data are inconsistent.Objectives: We examined associations between prenatal urinary concentrations of phthalate metabolites and neurobehavioral scores among children.Methods: We measured phthalate metabolite concentrations in urine samples from 153 pregnant participants in the Study for Future Families, a multicenter cohort study. Mothers completed the Child Behavior Checklist when the children we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(131 citation statements)
references
References 40 publications
7
123
0
1
Order By: Relevance
“…d Adjusted for: age of the child at the time of outcome assessment, sex, maternal education, maternal smoking during pregnancy, birth season, breastfeeding, country origin of the mother, number of siblings, maternal age. Kobrosly et al, 2014;Lien et al, 2015) (Table 1). In the present study the results obtained at the age of 4 and 7 years did not show evidence of an adverse effect of prenatal exposure to phthalates for any of the different outcomes assessed.…”
Section: Discussionmentioning
confidence: 99%
“…d Adjusted for: age of the child at the time of outcome assessment, sex, maternal education, maternal smoking during pregnancy, birth season, breastfeeding, country origin of the mother, number of siblings, maternal age. Kobrosly et al, 2014;Lien et al, 2015) (Table 1). In the present study the results obtained at the age of 4 and 7 years did not show evidence of an adverse effect of prenatal exposure to phthalates for any of the different outcomes assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational exposure to BPA increased play behaviors and social investigation in juvenile mice without impairing social recognition [29]; this effect was transgenerationally transmitted (without further treatments) up to the third generation of mice (F3), which also showed decreased social recognition, suggesting an epigenetic effect of BPA exposure via the germ line [17,18]. Human epidemiological studies report sex-dependent associations between gestational BPA and phtalates with aggressive behaviors in children and adolescents [20,22,30,31]. …”
Section: Behaviormentioning
confidence: 99%
“…Experimental animal studies have shown that prenatal DEHP and di-n-butyl phthalate can lead to impaired spatial learning and memory, and decreased grooming behavior (Hoshi and Ohtsuka, 2009; Tanaka, 2002; Li et al, 2009). Epidemiological studies report that urinary concentrations of low molecular weight phthalate metabolites, such as mono-n-butyl phthalate (MnBP) and monoisobutyl phthalate (MiBP), measured during the 2nd and 3rd trimesters of pregnancy were associated with neonatal behavior and reflexes (Yolton et al, 2011; Engel et al, 2009), aggression, rule breaking, and conduct problems (Engel et al, 2010; Whyatt et al, 2012; Kobrosly et al, 2014; Lien et al, 2015), autistic traits (Miodovnik et al, 2011), lower mental and psychomotor development (Whyatt et al, 2012; Balogh et al, 2011), emotional problems (Whyatt et al, 2012) and reduced IQ (Factor-Litvak et al, 2014); whereas others have not (Braun et al, 2014; Huang et al, 2015; Gascon et al, 2015). …”
Section: Introductionmentioning
confidence: 99%